HOW GREEN AWARENESS GREEN KNOWLEDGE OF GEN Z IMPACTED ATTITUDE TOWARD GREEN SHARIA BANKING AND INTENTION TO USE SERVICES GREEN SHARIA BANKING - Solekah, Nihayatu Aslamatis; Prayogi, Adha Herfian (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2024)
This study aimed to determine the relationship between green awareness, green knowledge on attitude toward green sharia banking and Intention to use services sharia banking yang menerapkan green banking in Malang City. Purposive sampling was used in this study using a sample of 194 participants. Data analysis checks using a statistical model utilizing the SmartPLS 4 program for the structural-partial least square (SEM-PLS) model. The results of this study indicate that green awareness and green knowledge affect attitude toward green sharia banking and intention to use services green sharia banking. But attitude toward green sharia banking has no effect on intention to use green sharia banking services. The results of this research provide the implication that awareness and knowledge about Gen Z green Sharia banking practices contribute directly to attitudes and intentions to use green Sharia banking services. Green awareness and knowledge are important factors shaping consumer attitudes and intentions towards green Islamic banking. Improving these two aspects can encourage wider adoption of green Islamic banking services, as more aware and knowledgeable consumers will better support and choose services that align with sustainability and Sharia values